Selective YAP/TAZ inhibition in fibroblasts via dopamine receptor D1 agonism reverses fibrosis - Haak, Andrew J; Kostallari, Enis; Sicard, Delphine; Ligresti, Giovanni; Choi, Kyoung Moo; Caporarello, Nunzia; Jones, Dakota L; Tan, Qi; Meridew, Jeffrey; Diaz Espinosa, Ana M; Aravamudhan, Aja; Maiers, Jessica L; et al. (Science translational medicine, 2019)
Tissue fibrosis is characterized by uncontrolled deposition and diminished clearance of fibrous connective tissue proteins, ultimately leading to organ scarring. Yes-associated protein (YAP) and transcriptional coactivator with PDZ-binding motif (TAZ) have recently emerged as pivotal drivers of mesenchymal cell activation in human fibrosis. Therapeutic strategies inhibiting YAP and TAZ have been hindered by the critical role that these proteins play in regeneration and homeostasis in different cell types. Here, we find that the Gα -coupled dopamine receptor D1 (DRD1) is preferentially expressed in lung and liver mesenchymal cells relative to other resident cells of these organs. Agonism of DRD1 selectively inhibits YAP/TAZ function in mesenchymal cells and shifts their phenotype from profibrotic to fibrosis resolving, reversing in vitro extracellular matrix stiffening and in vivo tissue fibrosis in mouse models. Aromatic l-amino acid decarboxylase [DOPA decarboxylase (DDC)], the enzyme responsible for the final step in biosynthesis of dopamine, is decreased in the lungs of subjects with idiopathic pulmonary fibrosis, and its expression inversely correlates with disease severity, consistent with an endogenous protective role for dopamine signaling that is lost in pulmonary fibrosis. Together, these findings establish a pharmacologically tractable and cell-selective approach to targeting YAP/TAZ via DRD1 that reverses fibrosis in mice.